Postpartum hypertension - Velásquez, Jesús Arnulfo (Revista Colombiana de Obstetricia y Ginecología, 2005)
There are very few studies investigating about the physiology and pathology of the different puerperal changes that can induce the onset and appearance of the postpartum hypertension. Additionally there are not actual studies supporting the necessity for management protocols during this period, and the few available literature concerning these aspects has been based on non-organized random experience. The hypertensive conditions during pregnancy constitute a very important risk factor that may affect the odds for future development of cardiovascular disease and its related mortality. These conditions must be considered like either the beginning or the consequence of an unlimited amount of subtle clinic events yet ignored. In the preeclampsia cases the baby’s delivery is only a temporary solution for the crisis that was triggered by pregnancy, but it is not the definitive cure for the condition. Henceforth, it is necessary to establish adequate strategies to closely evaluate and follow these women’s health problems.